Documentation of prevailing agroforestry systems and socio-economic conditions of agroforestry farmers of Nyishi tribe: A case study of Papumpare district in Arunachal Pradesh, India. - Pangging, Govinda; Nabam, Api; Sharma, Madhubala (Indian Journal of Agroforestry, 2025)
The present study was conducted from 2020 to August 2022 in the Papumpare district of Arunachal Pradesh, India to document the prevailing agroforestry systems and socio-economic condition of agroforestry farmers belonging to Nyishi tribe. In this study, the highest family size, sex ratio and literacy rate were 9.25±3.5 observed in large farmers, 1:1.6 (small farmers) and 93% (marginal farmers), respectively. Farming was the dominant occupation amongst agroforestry farmers. The highest Adult Cattle Unit (ACU) and fodder requirement per HH was observed in large farmer. Six traditional agroforestry systems (AFS) were identified such as agri-silvipastoral system (homegarden), agri-silvicultural system, agri-silvi-horticultural system, aquaforestry, agri-silvicultural system and agri-horticultural system. Of these, the dominant AFS was agri-silvipastoral system (homegarden), followed by silvi-horticultural, agri-silvi-horticultural, etc. In total, 94 plants spp. with 79 genera belonging to 43 families reported from all AFS and the highest no. of species found in the agricultural component with 39 plant spp. followed by silvicultural crops (28 spp.) and horticultural crops (27 spp.). Among all AFS, agri-silvipastoral system had the highest species diversity with 79 spp., followed by agri-silvihorticultural system, silvihorticultural system, etc. The highest average area per HH was recorded in 6 AFS viz., agri-silvipastoral system, agri-silvihorticultural system, silvihorticultural system, agrisilvicultural system and aquaforestry system were 0.277ha highest in semi-medium farmers, 4.9ha (large farmers), 1.956ha (large farmers), 3.5ha (large farmers) and 1ha (large farmers), respectively.